Nutraceutical support for respiratory diseases - Yu-Ya Hwang; Yuan-Soon Ho (Food Science and Human Wellness)
Respiratory diseases have been a major health concern for human beings since several decades. Soothing the irritated nasal passages and airways had been a mutual necessity in multiple ancient cultures. In ancient China, herbs were largely used to help deal with cough and reduce mucus, thereby maintaining respiratory health. In India, knowledge of herb-related remedies passed down through generations. In the human society, freshly prepared herb ointments, including air-dried herbs, and boiled herbal soups have had a long history of combining botanical nutrients with local cuisine.Although the use of herbs and natural products from plants (NPFPs) has been primarily cited in reviews based on modern respiratory diseases, the concept of soothing and alleviating disease progression or reducing mucus production has been highly valued. Nevertheless, only a few herbs could directly disrupt the irreversible fibrotic progression. On the other hand, natural products from animals (NPFAs) have more potential in disrupting procollagen or extracellular matrix deposition. Due to these reasons, NPFAs could be considered as important functional foods for patients with respiratory diseases. In this article, we provide a review of both NPFAs and NPFPs that are adjuvant to respiratory health. Keywords: Respiratory disease, NPFP, NPFA, Nutrition, Antioxidants